2014
DOI: 10.1103/physrevlett.113.107002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Quenched Oxygen Disorder on Charge Density Wave Order inYBa2Cu3O6+x

Abstract: The competition between superconductivity and charge density wave (CDW) order in underdoped cuprates has now been widely reported, but the role of disorder in this competition has yet to be fully resolved. A central question is whether disorder sets the length scale of the CDW order, for instance by pinning charge density fluctuations or disrupting an otherwise long range order. Using resonant soft x-ray scattering, we investigate the sensitivity of CDW order in YBa2Cu3O6+x (YBCO) to varying levels of oxygen d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 37 publications
2
58
0
Order By: Relevance
“…6 Another discrepancy exists with Ref. 9, where S CDW was found to decrease upon increasing the amount of oxygen disorder.…”
Section: Discussionmentioning
confidence: 51%
“…6 Another discrepancy exists with Ref. 9, where S CDW was found to decrease upon increasing the amount of oxygen disorder.…”
Section: Discussionmentioning
confidence: 51%
“…The sample [19] was single-crystal YBa 2 Cu 3 O 6+x with ortho-III oxygen ordering [20], with x = 0.75. The critical temperature (T c ) for the superconducting transition is 75.2 K and the doping level is p = 0.133.…”
Section: Methodsmentioning
confidence: 99%
“…The high-quality detwinned single crystals of YBCO are platelets with the broad face perpendicular to the c axis, and were measured with the polarization along either the a or b crystallographic directions. The CDW transition temperature T CDW was found to occur at ∼150 K using resonant x-ray scattering [20]. Strong, single-cycle THz pulses were generated from a LiNbO 3 crystal via optical rectification of 800 nm femtosecond laser pulses using the tilted-phase front technique [21].…”
Section: Methodsmentioning
confidence: 99%
“…• In addition to these aspects, a recent study by Achkar et al [47] directly showed that the CDW correlations are to a large degree unaffected upon disordering the CuO chains, and therefore are intrinsic to the CuO 2 planes. This once again validates the scenario where the ordering mechanisms in the planes are largely insensitive to the phenomenology in the chain layer, where the orthorhombicity originates from.…”
Section: Supplementary Textmentioning
confidence: 99%